Peran QRIS dalam Meningkatkan Inklusi Keuangan pada Lembaga Bank dan Non-Bank di Indonesia: Systematic Literature Review - Lailatul Maulida; Alyaa Destra A.f; Serli Febriyanti; Achmarul Fajar (PT. Hasba Edukasi Mandiri, 2026)
The development of digital payment systems in Indonesia has encouraged the increasing use of the Quick Response Code Indonesian Standard (QRIS) as a non-cash transaction tool. This study aims to analyze the role of QRIS in improving financial inclusion in banking and non-banking institutions in Indonesia. The research method used is a Systematic Literature Review (SLR) with a qualitative descriptive approach through the analysis of various journals and scientific articles related to QRIS, fintech, and financial inclusion. The results show that QRIS plays an important role in facilitating access to financial services, improving the efficiency of digital transactions, and supporting the development of MSMEs and the digital economy in Indonesia. In addition, collaboration between banking and non-banking institutions through QRIS is able to create a more inclusive and efficient payment system. However, the implementation of QRIS still faces challenges such as low public digital literacy, limited technological infrastructure, and digital transaction security. Therefore, increasing public education and strengthening digital infrastructure are necessary to support the optimization of QRIS usage in improving financial inclusion in Indonesia.